Yeast vaccine production platform for human and animal infectious diseases - Ramos-Vega, Abel; Monreal-Escalante, Elizabeth; Bañuelos-Hernández, Bernardo; Angulo, Miriam; Trujillo, Edgar; Angulo, Carlos (Frontiers in Immunology, 2025)
Yeasts have contributed to human and animal health through functional antigen production for vaccine formulations. Some yeast-made vaccines have become a reality for humankind because they have reached commercialization (hepatitis B, HPV, and tick parasitosis). Many other vaccine prototypes are under preclinical and clinical evaluations, hoping for their usage soon. Currently, genomes, genetic modification techniques, and industrial vaccine manufacturing have been successfully developed for Saccharomyces cerevisiae, Komagataella phaffii (formerly Pichia pastoris), and Hansenula polymorpha. Moreover, several yeast species are under research as prospects for vaccine production systems, such as Kluyveromyces lactis, Yarrowia lipolytica, Schizosaccharomyces pombe, Saccharomyces boulardii, and Komagataella phaffii. This review was mainly focused on commercial human and animal vaccines, describing and discussing genetic engineering tools, downstream antigen purification processes, GMP according to regulatory issues, and identifying challenges and future directions on the use of yeast as a vaccine production platform to fight against infectious diseases.